YIELD PERFORMANCE AND STORAGE BEHAVIOUR OF EARLY BULKING POTATO HYBRIDS IN NORTH-WESTERN PLAINS OF INDIA - Kang, G. S.; Kumar, Raj; Pandey, S K (Potato Journal, 2013)
Four early bulking hybrids, viz., J.96-84, J.96-99, J.96-149 and J.96-238 were bred for northern plains. These were assessed for four years in replicated yield trials for tuber yield at 60 and 75 days harvest and other tuber characteristics. These hybrids had 11.9 to 16.8% higher tuber yields than the best control Kufri Ashoka at 75 days. All the 4 hybrids possessed acceptable tuber characters and keeping quality.